Green synthesis and characterization of Pullulan mediated Silver nanoparticles through ultraviolet (UV) virradiation - Khan, Muhammad Jamshed; Kumari, Suriya; Shameli, Kamyar; Selamat, Jinap; Sazili, Awis Qurni (MDPI AG, 2019)
Nanoparticles (NPs) are, frequently, being utilized in multi-dimensional enterprises. Silver nanoparticles (AgNPs) have attracted researchers in the last decade due to their exceptional efficacy at very low volume and stability at higher temperatures. Due to certain limitations of the chemical method of synthesis, AgNPs can be obtained by physical methods including sun rays, microwaves and ultraviolet (UV) radiation. In the current study, the synthesis of pullulan mediated silver nanoparticles (P-AgNPs) was achieved through ultraviolet (UV) irradiation, with a wavelength of 365 nm, for 96 h. P-AgNPs were formed after 24 h of UV-irradiation time and expressed spectra maxima as 415 nm, after 96 h, in UV-vis spectroscopy. The crystallographic structure was “face centered cubic (fcc)” as confirmed by powder X-ray diffraction (PXRD). Furthermore, high resolution transmission electron microscopy (HRTEM) proved that P-AgNPs were covered with a thin layer of pullulan, with a mean crystalline size of 6.02 ± 2.37. The average lattice fringe spacing of nanoparticles was confirmed as 0.235 nm with quasi-spherical characteristics, by selected area electron diffraction (SAED) analysis. These green synthesized P-AgNPs can be utilized efficiently, as an active food and meat preservative, when incorporated into the edible films.